Asymptotic Computational Fluid Dynamic (ACFD) Study of Three-Dimensional Turning Diffuser Performance by Varying Angle of Turn - Tham, Wei Xian; Nordin, Normayati; Hariri, Azian; Nasir, Nurul Fitriah; Mat Isa, Norasikin; Yahya, Musli Nizam; Md. Seri, Suzairin (International Journal of Integrated Engineering, 2019)
The present work aims to numerically investigate the effect of varying turning angle, ø = 30° - 180° on the performance of 3D turning diffuser and to develop the performance correlations via integrating the turning angle using Asymptotic Computational Fluid Dynamics (ACFD) technique. Among all the turbulence models examined, the best validated results were obtained with the Reynold Stress Model with enhanced wall treatment of =1.0 was applied for the intensive simulation. As the turning angle increased from 30˚ to 180˚, the pressure recovery was reduced by 89.3% and the flow uniformity index was raised by 27.7%. Minimal flow separation took place at 0.75 of 90˚ turning diffuser whereas maximum flow separation happened at 0.44 of 180˚ turning diffuser. The performance correlations of 3D turning diffuser as a function of geometrical and operating parameters was successfully developed using ACFD method. The ACFD results were kept within ±11.4% of deviation when compared with both CFD and experimental results.